A Multiplex PCR for Detection of hlyA, papC, and traT genes in multidrug resistance Escherichia coli isolated from pregnant women - Ruqaia Sabbar Salman; Mun'im Radwan Ali; Suzan Saddi Hussin (College of Pharmacy / Mustansiriyah University, 2013)
Urinary tract infection (UTI) in pregnancy is a common clinical problem which causes morbidity and, in a small minority of cases, renal damage and chronic renal failure. Urine samples from three hundred pregnant women were collected from Baghdad Teaching Hospital, were examined between January to June 2012 for the presence of bacteria. Their ages ranging from 15 to 50 years. Up to 32.6% (98) of women have a urinary tract infection (UTI). Escherichia coli was detected in 27.5% (27) of all the urine samples. All isolates were screened for some virulence factors: α-haemolysin, adhesion factor type P fimbriae and serum resistance. Multiplex PCR systems were used to detect genes encoding α-hemolysin (hlyA), adhesion P(papC), and traT associated with serum resistance. The results indicated that the occurrence of papC was detected in (18.5%), while traT was detected in (96.2%) of isolates on the other hand hlyA can't detected in any E. coli isolates. All the isolates were also studied for antibiotic susceptibility pattern using a disc diffusion method. The rate of resistance of E. coli Amoxicillin (92.5%), Amoxicillin/Clavulanic acid (89%), Cefotazidime, Cefotaxime and Cefepime (78%), kanamycin (59%), levofloxacin (55.5%), Ciprofloxacin (52%) and showed high degree of sensitivity toward Cefoxitin and Imipenem (7% and 0%) respectively. Additionally,17 (62.9%) isolates were multidrugresistant. The finding of this study indicated that the traT widespread among pathogenic E. coli in Iraq. Furthermore it concludes that E. coli is one of the important multidrug resistance causative agents of urinary tract infection in young women especially during the state of pregnancy.